The Effectiveness of Podcasts in Improving High School Students' Speaking and News Text Writing Skills (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Traditional textbook-based language instruction in Indonesian secondary education shows limited effectiveness in developing integrated speaking and writing competencies, particularly in news text production. While previous research examined podcast effectiveness in single-skill development, a significant gap exists in understanding how podcast-based instruction simultaneously enhances both abilities through unified pedagogical approaches. This study investigates podcast media effectiveness in developing integrated language skills among Indonesian high school students, addressing the theoretical void in cross-modal transfer research. The research employed pure experimental design with randomized pretest-posttest control group methodology, involving 72 Grade XI students from SMAN 19 Gowa randomly assigned to experimental (podcast-based) and control (textbook-based) groups. Data collection utilized validated rubrics with inter-rater reliability coefficients of 0.85 and 0.82 respectively. Results demonstrated significant improvements in both skill domains following podcast intervention. Speaking skills showed substantial enhancement in the experimental group (M = 47.00 to 80.22, t = 16.092, p < 0.001) compared to control group gains (M = 46.22 to 60.00). Writing competencies similarly improved significantly (M = 43.81 to 69.53, t = 6.963, p < 0.001) versus control group progress (M = 44.89 to 61.94). The findings reveal that podcast-based instruction facilitates cross-modal transfer mechanisms, where auditory input enhances written production through schema activation and cognitive load optimization. Educational implications include curriculum integration recommendations for technology-enhanced language learning and teacher training program development for multimedia pedagogy implementation.